The effects of hot-deboning on the physical meat quality and microbial quality and safety of ostrich (Struthio camelus) meat - Pretorius, Karla (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScFoodSc)--Stellenbosch University, 2019.